Suicidal deaths in childhood and adolescence - (:unkn) unknown (ELSEVIER IRELAND LTD, 2004)
Suicide has been reported as the second or third most common cause of death in children and adolescents worldwide. In this study, cases of under the age of 19 years submitted to the Institute of Forensic Medicine, First Specialization Board between 1996 and 2000 as suicides by the Board were evaluated retrospectively. The cases included in this study were the cases bearing locally questionable components, so had been submitted to the evaluations by the Board in order to eradicate the doubts. A total of 43 cases were investigated regarding age, gender, cause of death, manner of death, place. of death, time of death, and the risk factors. Of the 43 cases evaluated, 31 cases were female and 12 cases were male. The notable suicide method was found to be firearms. Although it was clear that that not all of the suicide cases in this age group had been submitted to the Institute of Forensic Medicine, the most striking result of this study, nevertheless, was that girls constituted the 72% of suicidal deaths in this age group. (C) 2003 Elsevier Ireland Ltd. All rights reserved.
Keywords: World Health Organization; suicidal deaths; suicide method; RISK-FACTORS; PSYCHOLOGICAL AUTOPSY; COMPLETED SUICIDE; SUBSTANCE-ABUSE; CHILDREN; FAMILY; INJURIES; BEHAVIOR; IMPACT; MANNER